A transnational regioscape in the making. The Baltic Sea in Christian Petzold’s Barbara and Ilze Burkovska-Jacobsen’s My Favorite War - Mrozewicz, Anna Estera (Folia Scandinavica Posnaniensia, 2023)
The Baltic Sea has effectively separated the Scandinavian and Eastern European countries, especially in the period when this body of water constituted a part of the Iron Curtain and functioned for Scandinavians as an imaginary protective moat. From the East-Central European perspective, the Baltic Sea offered a hope of escape to freedom, encapsulated in the cinematic trope of the sea as a ‘blue boundary’, or a ‘horizon of hope’. But the Baltic Sea was also feared as a life-threatening border, as expressed in the trope of ‘Baltic noir’, a variation of the ‘Eastern noir’ trope (Mrozewicz 2018) – imagining the sea in nocturnal scenery as wild and under state control. The article discusses screen representations of the Baltic Sea understood as performative regioscaping practices (Chow 2021), offering insights into the memories and histories of human mobilities across the Baltic Sea beyond official narratives, as well as into the human relationship with the sea as both a cultural boundary and material body of water. As demonstrated by the analyzed film examples, Christian Petzold’s Barbara (2012, Germany) and Ilze Burkovska-Jacobsen’s My Favorite War (2020, Norway, Latvia), the Baltic Sea continues to be an important spatiotemporal node in the transnational re-telling of the region’s history and identity.